CONTEXTUAL PROBLEMS OF DIFFERENTIATING OF ENGLISH LANGUAGE SYNONYMS IN THE TERM-SYSTEM ASPECT - Oblokulova F.Z.; Oblokulova Feruza Zayniddin kizi (World Scientific Research Journal, 2025)
Abstract: The richness of the English language often leads to challenges in distinguishing synonyms, especially within specialized terminology. This article explores the contextual difficulties involved in differentiating words that appear to be interchangeable in technical fields. True synonymy is uncommon, as subtle semantic distinctions, shaped by specific connotations of fields, register, and collocational limitations, significantly influence meaning within controlled vocabularies. The dependence on shared implicit knowledge among experts further complicates the accurate differentiation of synonyms. The article examines the issues arising from ambiguous definitions, the absence of standardization, and the dynamic nature of terminology in term systems. Through illustrations from engineering, science, and social sciences, the article delves into the intricacies of selecting between synonyms, stressing the potential for misunderstandings and mistakes. It concludes by highlighting the necessity for a nuanced grasp of linguistic and contextual elements to ensure effective communication in specialized areas. Additionally, it investigates how linguistic, situational, domain-specific, and cultural contexts undermine the clear boundaries of synonymous terms, affecting consistency, clarity, and knowledge transfer. The article wraps up by emphasizing the vital importance of context-sensitive methodologies to alleviate these differentiation challenges.